Web-Based Geographic Information System For Mapping Non-Metallic Mineral And Rock Mining In North Central Timor Regency - Elenora naiobe; Yoseph Pius Kurniwan Kelen; Anastasia Kadek Dety Lestari (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2026)
The monitoring and dissemination of information regarding non-metallic mineral and rock mining locations in North Central Timor (TTU) Regency remain constrained by conventional, non-digital data collection systems. This study aims to develop a web-based Geographic Information System (GIS) capable of accurately and integrally mapping and presenting mining locations in TTU Regency. This applied research employs a Prototype development model, integrating the Google Maps API for interactive spatial visualization and a role-based data entry mechanism to separate admin and user functions. Black-box Testing results confirm that all functions on both admin and user sides operate as specified, enabling the digitization of mining attribute data (e.g., IUP SK numbers, area size, operational status). The main contributions of this study are: (1) improving the efficiency of mining data management at the ESDM Branch Office Region I, and (2) providing more transparent, real-time public access to mining location information, thereby addressing the limitations of conventional systems.